Self-uniqueness beliefs and adherence to recommended precautions. A 5-wave longitudinal COVID-19 study. (January 2023) - De Witte, Dries; Delporte, Margaux; Molenberghs, Geert; Verbeke, Geert; Demarest, Stefaan; Hoorens, Vera
Abstract: Rationale: Research on health-related self-uniqueness beliefs suggested that these beliefs might predict adherence to precautions against COVID-19. Objective: We examined if comparative optimism (believing that one is less at less than others), self-superiority (believing that one already adheres better to precautions than others), and egocentric impact perception (believing that adverse events affect oneself more than others) predicted intended adherence to precautions. Method: We measured self-reported intentions, optimism for self and others, perceived past adherence by self and others, and perceived impact of the measures and the disease on self and others in a 5-wave longitudinal study in December 2020–May 2021 (N ≈ 5000/wave). The sample was in key respects representative for the Belgian population. We used joint models to examine the relationship between self-uniqueness beliefs and intended adherence to the precautions. Results: Believing that COVID-19 would affect one's own life more than average (egocentric impact perception) was associated with higher intentions to adhere to precautions, as was believing that the precautions affected one's life less than average (allocentric impact perception). Self-superiority concerning past adherence to precautions and comparative optimism concerning infection with COVID-19 were associated with higher intended adherence, regardless of whether their non-comparative counterparts (descriptive norm, i.e., perceived adherence to precautions by others, and personal optimism, respectively) were controlled for. Comparative optimism for severe disease and for good outcome were associated with lower intended adherence if personal optimism was not controlled for, but with higher intended adherence if it was controlled for. Conclusion: Self-uniqueness beliefs predict intended adherence to precautions against COVID-19, but do so in different directions. Highlights: Self-uniqueness beliefs about the risk and prevention of COVID-19 are widespread. Egocentric perception of the impact of COVID-19 predicts adherence to precautions. Egocentric perception of the impact of precautions predicts lower adherence to them. Comparative optimism predicts higher, rather than lower adherence to precautions. Illusory superiority concerning past adherence predicts higher intended adherence.